Hubungan Kadar Troponin-I Dengan Serum Glutamic Oxaloacetic Transminase (Sgot) Pada Penderita Infark Miokard Akut - Ibrahim, Ibrahim; Pricilia, Adelva; Setya Prima, Heppy (Universitas Sumatera Barat, 2024)
Acute Myocardial Infarction (AMI) is a condition where blood flow in the coronary arteries stops due to thrombus obstruction, resulting in insufficient oxygen supply to the myocardium, resulting in an imbalance between myocardial oxygen supply and demand, causing myocardial cell necrosis or death. Inhibited, causing cardiac ischemia. The aim of this study was to determine the relationship between troponin-I levels and serum glutamic acid oxalacetic aminotransferase (SGOT). The research method used is retrospective and descriptive analysis. This research was conducted at RSUP Dr. M. Djamil Padang, 75 patients were recorded in 6 months (January to June) 2022. The sampling technique used total sampling technique. Data were analyzed using univariate and bivariate tests using correlation tests. The average troponin I level in this study was 766.28 ng/L and the average SGOT level was 87.04 U/L. The Sig value indicates a weak relationship between troponin I levels and SGOT in acute myocardial infarction patients. = 0.012 (p>0.05). There is a moderate relationship between troponin-I levels and SGOT in acute myocardial infarction patients, with a correlation coefficient of 0.311 (r = 0.26 – 0.50 moderate relationship). It is hoped that future researchers will serve as a reference as basic research for future research.